Comprehensive Review of Wearable Antennas With Flexible Periodic Structures for Body-Effect Mitigation - Adel Ashyap; Raad Raad; Faisel Tubbal; Wajid Ali Khan; Suhila Abulgasem (IEEE Access)
Recent advancements in wireless technology have prompted the development of wearable antennas, particularly for Wireless Body Area Networks (WBANs) used in sports, military activities, healthcare, and identification systems. Unlike traditional antennas, wearable antennas operate very close to the curved human body. Consequently, their performance metrics such as reflection coefficient, bandwidth, radiation characteristics, efficiency, gain, directivity, and Specific Absorption Rate (SAR) can be significantly affected by interactions with human body tissues. To address these challenges, periodic structures are integrated into wearable antenna designs to mitigate the effects of coupling and absorption by the human body. To date, a limited number of works have surveyed, compared, and categorized the proposed wearable antenna designs integrated with periodic structure based on their operating frequency bands and their interactions with the human body. To this end, this paper contributes to the literature by detailing the selection of materials, highlighting the limitations of wearable antennas, characterizing the periodic structures, elaborate on dielectric properties data of human body models, discussing the influence of periodic structures on antenna performance and their significance in isolating them from the human body. Furthermore, this study provides an in-depth review of 81 papers evaluating the performance of antennas integrated with periodic structures, both in free space and on the human body, across single-band, dual-band, and triple-band designs. The selected papers were chosen based on their publication in reputable journals, the quality of their research, and the comprehensiveness of their data analysis. In addition, it provides a summary of several common flexible materials used in wearable antennas with their electrical properties as well as the dielectric properties of the human body for different frequencies. Moreover, it discusses the challenges and considerations involved in designing appropriate wearable antennas.